Faktor-Faktor Penyebab Tidak Terdaftarnya Hak Tanggungan - Nurul Syazwani Sabang; Mutia Cherawaty Thalib; Mohamad Taufiq Zulfikar Sarson (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to find out what the legal consequences are of bad credit agreements where mortgage rights are not registered at the Gorontalo City National Land Agency office and to find out the factors that cause mortgage rights not to be registered. The type of research used is Normative Empirical research, using data types consisting of primary data, secondary data and tertiary data. Data collection techniques were carried out using interview, observation and literature techniques. Then the data is analyzed descriptively or provides an overview or explanation of the research subjects and objects as the results of the research conducted. The results of this research show that cases of bad credit agreements where mortgage rights were not registered at the national land agency office have occurred in the city of Gorontalo. So the legal consequence obtained from this case is that the bank as the creditor cannot prosecute in court because the mortgage which is used as collateral is not registered. Clearly this is detrimental and does not provide legal certainty for both parties concerned, especially because registration of mortgage rights determines the birth of mortgage rights. Then there are several factors that cause the mortgage rights not to be registered, namely, negligence on the part of the land owner, administrative obstacles, financial difficulties, approval from related parties and so on.